Pemberian Posisi untuk Mengatasi Masalah Pengosongan Lambung pada Bayi Prematur - Natalia Devi Oktarina; Yeni Rustina; Defi Efendi (Poltekkes Kemenkes Bengkulu, 2020)
Gastric emptying in premature infants is slower than aterm infant aterm for 12 hours and some cases reach 22-36 hours. This slow emptying of the stomach causes to increase the volume of gastric residual and raising the risk for infants to experience gastroesophageal reflux, vomiting, aspiration and necrotizing etherocolitis. This study aims to analyze the effectiveness of positioning on gastric emptying show from gastric residual in premature infants in the Perinatology RSUPN Cipto Mangunkusumo. The research design used in this research is quasi experiment on 20 premature infants with consecutive sampling technique. The data analysis used Wilcoxon test for gastric residual. The study showed a difference in average abdominal distensionand gastric residual in right lateral position, left lateral positions and pronation is significant so that it can be concluded effective positioning to accelerate gastric emptying. Based on these results then the positioning can be recommended to be an alternative nursing care in overcoming the problem of gastric emptying in premature infants.